Evaluasi Sistem Pelaporan Kinerja Sebagai Instrumen Penjaminan Mutu Eksternal Di Madrasah Diniyyah Al-amiriyyah - Umam, Septian Khoirul; Fauzi, Moh. Nur (ProBisnis : Jurnal Manajemen, 2024)
This study aims to analyze the performance reporting system as an external quality assurance instrument so that Islamic schools can produce quality output. The performance reporting system at Islamic schools has been proven to function as an important tool in providing constructive feedback from external parties, such as accreditation institutions and the community. The type of research is qualitative with a case study design, the informants concerned include: the head of the school, teachers, quality/accreditation supervisors, Islamic boarding school caretakers, data collection techniques using: interviews, observation, documentation. Data analysis uses triangulation and data validity uses an interactive model. The results of the study show 1) standardization of education quality, 2) transparency and accountability, 3) feedback for continuous improvement. The implementation of the performance reporting system at Islamic schools not only supports the achievement of accreditation, but also creates a culture of continuous improvement that is responsive to the needs of students and the community, thereby improving the overall quality of education. Data analysis uses triangulation and data validity uses an interactive model.